How do Millennial retail shopping habits for animal feed differ from that of other generations? - Lincoln, Jennifer (Kansas State University, 2018)
Competition in the retail animal feed business can be challenging. Millennials are emerging as an increasingly important consumer group. Companies want to attract Millennials as new customers while at the same time retaining current customers of Baby Boomers and Gen X generations. Consequently, an important question is how do Millennial retail shopping habits for animal feed differ from that of other generations. To help answer this question the thesis research utilizes customer survey data obtained, from the Kent Nutrition Group. The data was collected through an online survey which was conducted with customers from Company W’s customer list. The total sample consists of 1068 customers. The data is analyzed using exploratory data analysis to gain insights on key differences and important attributes related to marketing and selling to customers from different generation groups. The results indicate that word of mouth serves as the largest initial source of awareness for all customers. Not surprisingly, the results show higher tendency to shop online and a preference for social media as a source of information by Millennials compared to Baby Boomers and Gen X customers. Knowledgeable staff and a positive in-store shopping experience continue to be a high priority for all customers. In general, e-mail or a mailed newsletter were identified as important communication methods by respondents of all generations. The results also show high preference by customers of all generations for receiving sales circulars and tips for animal and pet care. Sales circulars, direct mailers and newspaper ads are the core communication channels that customers view advertising from Company W. Three quarters of Company W’s customers expressed some level of interest in shopping online through Company W if the option were available. This implies that offering online shopping options will not only enhance the current customers’ experience but also attract new customers. The gained insights will be used by Company W to adapt and enhance their marketing and sales strategies to a) effectively engage and attract more Millennial customers and b) improve retention and service for customers of Baby Boomers and Gen X generations. The researcher will use the insights gained from this study to improve marketing efforts for the Kent Nutrition Group.
Keywords: Millennial; Consumer Preference; Animal Feed; Purchasing Power; Demographics; Animal Health